UPAYA PENGONDISIAN KELAS UNTUK MENDISIPLINKAN SISWA DALAM PEMBELAJARAN - Hisbullah Huda; Masykurotin Azizah; Dina Hidayatus Sholikhah; Umilatur Rosidah; Satrio Wicak Iktiarto (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2021)
This research is a form of teacher effort to condition the class to be more disciplined in learning. This research was taken in quantitative research to find out the causes of the problems faced by teachers in conditioning the class or classroom management of the Roudlotul Qur'an Integrated Mts students. This research is a form of field research involving students from grades VII, VIII and IX. The data collection technique is through observation, questionnaires and documentation. Data can be analyzed from each class. The subjects studied are teachers in each subject and students from class VII, VIII and IX.As for the results achieved: the teacher's efforts to make the class conducive and calm, learning can be followed smoothly, avoiding chaos and noise, playing alone with colleagues, permission to leave when teaching and learning activities are active and the main thing is to improve student discipline. Methods that can be used include: implementing learning strategies, classroom management and spatial planning, motivating students, playing games or can be interspersed with ice breaking to condition students. Basically class management in the form of classroom conditioning also affects the ongoing learning process. If teachers are not able to master classroom management efforts, the learning process will be disrupted and it will be difficult to achieve educational goals.